PENDIDIKAN NAHDLATUL ULAMA UNTUK PERADABAN DUNIA (RESPON K.H. ABDUL WAHID HASYIM) - Deden Saeful Ridhwan; Novri Dewita (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2020)
Kiayi Wahid Hasyim, a reformist pro-change, proposed changes and at the same time did the same for the pesantren environment. The most monumental changes in Pondok Pesantren Tebuireng, reforms in the methods and objectives of learning at the pesantren, and the establishment of madrasas. Kiayi Wahid Hasyim made the system tutorial as a bandongan method session. According to him, the bandongan method is very ineffective for the initiative of the students. Few things are aware that Kiayi Wahid Hasyim is a traditionalist who claims to be futuristic. He is a figure who represents circles that are rarely touched by academics, even researchers, most of whom are Western researchers, who tend to fall in love with modernists who are dynamic, adaptive, pragmatic, and not at all hostile to those from the West.